How Do People Respond to Local Governments in Communicating Government Programs Through Social Media? - Mulyaningsih Mulyaningsih (Jurnal Manajemen Indonesia, 2022)
Open communication is one of the government's efforts to meet the demands of society in creating more transparent public information services. Instagram is one of the social media that allows the government and the public to interact through two-way communication, creating and sharing content in the form of words, images, audio or video, in real time. This study aims to identify the community's response to the communication of local leaders in informing government programs through Instagram. This study focuses on the Indonesian government's program on the issue of public education through the New Student Admission program. This study used an exploratory sequential mixed-method. The data was obtained from public comments via Instagram on posts submitted by the head of the West Java region. A total of 867 comments are analyzed in this study. Data processing techniques using text mining with sentiment analysis approach. The study found that the activeness of local leaders in using Instagram to inform government programs was very effective and able to attract participation from the community. The majority of comments showed negative sentiment towards government program information regarding the new student admission program which was conveyed through the West Java regional head's Instagram. Keywords: open communication, Instagram, participation, public services, transparency